2017
DOI: 10.1021/acssuschemeng.7b03018
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Biocatalytic Activity toward Sterically Bulky Substrates in CO2-Expanded Biobased Liquids by Tuning the Physicochemical Properties

Abstract: The study of CO 2-expanded liquids using a green component such as a biobased solvent has been recently raised as a new concept for an alternative solvent and yet been largely unexplored in the literature for neither fundamental nor application studies. On the other hand, structural bulkiness of substrates remains one of the main limitations to promote enzymes as an efficient versatile catalytic tool for organic synthesis, especially biocatalysis in nonconventional solvents. Herein, we report a detailed invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…The phase equilibria and polarity measurements were performed by using the experimental equipment used in our previous studies. 21 Briefly, a high-pressure variable-volume view cell (9.6-31.3 cm 3 , Top Industrie, France) equipped with three sapphire windows and a magnetic stirrer ( Figure 1) and a 260D high-pressure Teledyne Isco syringe pump (the precision of the injected volume is ±1 cm 3 ). The temperature of the cell was kept at the desired value by a thermostatic bath and measured by a thermocouple (J type, precision of ±0.1 K) placed inside of the cell.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The phase equilibria and polarity measurements were performed by using the experimental equipment used in our previous studies. 21 Briefly, a high-pressure variable-volume view cell (9.6-31.3 cm 3 , Top Industrie, France) equipped with three sapphire windows and a magnetic stirrer ( Figure 1) and a 260D high-pressure Teledyne Isco syringe pump (the precision of the injected volume is ±1 cm 3 ). The temperature of the cell was kept at the desired value by a thermostatic bath and measured by a thermocouple (J type, precision of ±0.1 K) placed inside of the cell.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The higher solubility of CO 2 in 2-MTHF relative to that in water can be explained by a comparison of the Kamlet−Taft values (π*) for both solvents. 55 Hoang et al 54 With a consideration of the quadrupole moment in P4/P6, the binary subsystem CO 2 /2-MTHF can be described solely on the basis of pure chemical species parameters within our reported uncertainty. We attempted to model binary system CO 2 /2-MTHF with Aspen PC-SAFT based on pure chemical species parameters only.…”
Section: Journal Of Chemical and Engineering Datamentioning
confidence: 75%
“…Solubility data for CO 2 in the liquid phase of binary system CO 2 /2-MTHF at 293 K. Experimental data from the present work (▲) and from ref (△). Calculated values from the P4/P6 model () and with adjusted value for k ij in the A6 model (blue −–−).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Hence, the use of 2-Me-THF in the synthesis not only facilitated the sepa- reported that 2-Me-THF has a higher CO 2 solubility in the reaction system than water under identical experimental conditions [23]. Jessop and Matsuda et al showed that 2-Me-THF has lower values of Kamlet-Taft parameters such as polarizability, π* (0.5-1.1), which further allowed for the higher solubility of hydrophobic CO 2 in 2-Me-THF than water [24,25]. Matsuda et al also further reported that CO 2 expanded 2-Me-THF, and other bio-based solvents turned out to be an excellent solvent media for biotransformation.…”
Section: Resultsmentioning
confidence: 99%